Use of serology and real time PCR to control an outbreak of bovine brucellosis at a dairy cattle farm in the Nile Delta region, Egypt. Issue 1 (December 2015) - Gwida, Mayada; El-Ashker, Maged; Melzer, Falk; El-Diasty, Mohamed; El-Beskawy, Mohamed; Neubauer, Heinrich
Abstract Background Bovine brucellosis remains one of the most prevalent zoonotic infections affecting dairy cattle in developing countries where the applied control programs often fail. We analyzed the epidemiologic pattern of bovine brucellosis in a dairy cattle herd that showed several cases of abortions after regular vaccination with RB51 (B. abortus  vaccine). In 2013 thirty dairy cows, from a Holstein-Friesian dairy herd with a population of 600 cattle, aborted five months post vaccination by a regular RB51 vaccine. Blood samples were drawn from milking cows and growing heifers, as well as heifers and cows pregnant up to 6 months. These samples were collected in June 2013 (n  = 257) and May 2014 (n  = 263) and were tested by real time (rt)-PCR as well as serological tests, in particular Rose Bengal Test (RBT), Enzyme-Linked Immunosorbent Assays (ELISA) and Fluorescence Polarization Assay. Tissue specimens were also collected from an aborted fetus and cultured. Isolates were subjected to bacteriological typing tests at the genus and species levels. Results Five months post vaccination with RB51 vaccine, Brucella (B.) DNA was detected in blood samples of cows by rt-PCR. The serological tests also revealed the spread ofBrucella field strains within the herd in 2013. FourBrucella isolates were recovered from specimens collected from the aborted fetus. These isolates were typed as follows: oneB. abortus RB51 vaccine strain and three isolates ofB. abortus field strain. The seropositive cows with positive rt-PCR might indicate an infection by theBrucella field strain; while the positive rt-PCR results from seronegative animals may either be due to circulating RB51 vaccine DNA in vaccinated animals or to circulating field strain in infected animals before seroconversion. Conclusion The results herein suggest that PCR can be a good supplementary tool in an outbreak situation, if an assay is available that can differentiate vaccine and field strains with a high analytical sensitivity. We recommend using RBT and ELISA in parallel in outbreak situations, to identify as many infected animals as possible during the initial screenings. This test procedure should be repeated for at least three successive negative tests, with one month interval.